How do pre‐existing normal faults influence rift geometry? A comparison of adjacent basins with contrasting underlying structure on the Lofoten Margin, Norway. (17th April 2019) - Henstra, Gijs Allard; Berg Kristensen, Thomas; Rotevatn, Atle; Gawthorpe, Robert L.
Abstract: Recent studies of natural, multiphase rifts suggest that the presence of pre‐existing faults may strongly influence fault growth during later rift phases. These findings compare well with predictions from recent scaled analogue experiments that simulate multiphase, non‐coaxial extension. However, in natural rifts we only get to see the final result of multiphase rifting. We therefore do not get the chance to compare the effects of the same rift phase with and without pre‐existing structural heterogeneity, as we may in the controlled environment of a laboratory experiment. Here, we present a case study from the Lofoten Margin that provides a unique opportunity to compare normal fault growth with and without pre‐existing structural heterogeneity. Using seismic reflection and wellbore data, we demonstrate that the Ribban Basin formed during Late Jurassic to Early Cretaceous rifting. We also show that the rift fault network of the Ribban Basin lacks a pre‐existing (Permian‐Triassic) structural grain that underlies the neighbouring North Træna Basin that also formed during the Late Jurassic to Early Cretaceous. Being able to compare adjacent basins with similar histories but contrasting underlying structure allows us to study how pre‐existing normal faults influence rift geometry. We demonstrate that in Lofoten, the absence of pre‐existing normal faults produced collinear fault zones. Conversely, where pre‐existing faults are present, normal fault zones develop strong "zigzag" plan‐view geometries.